MOVIE DISTRIBUTION CHANNELS: ADVANTAGES AND DISADVANTAGES - TIMOTIN, LUDMILA; MARGINEANU, VIRGIL (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică)
In the context of film distribution, the existing distribution channels play a significant role in connecting the filmmakers with the general public. These channels represent the ways in which films reach viewers and allow access to diverse cinematic creations. Distribution channels have witnessed a profound transformation in recent years. Traditionally, cinemas were the primary medium for film exhibitions, but with the rise of television, film festivals and digital platforms, the filmmakers now have a wide range of options to reach audiences. This paper explores the advantages and challenges associated with each distribution channel, highlighting unique characteristics. Distribution involves the use of various existing distribution channels, each with its own distinct characteristics, advantages and disadvantages.